LUAS PENYEBARAN DAN INTENSITAS KEBERADAAN ULAT KANTONG PADA CEMARA UDANG DI PANTAI SAMAS, BANTUL, YOGYAKARTA - , NOVITA KRISTANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Coast sheoak (Casuarina equisetifolia) is fast-grow forest plant that can grow in critical area for rehabilitation. In Samas coast, Bantul, Yogyakarta the plant was planted for rehabilitation and for wind breaker in coastal area. Monoculture cultivation has potential to increase presence of plant disturbing organism. Bag worm is one of disturbing organism having polyfag characteristic that have high potential to destruct coast sheoak in Samas coast. Objective of this research was to identify distribution area and intensity of bag worm in coast sheoak with different age range and different location and distance from coast. Survey was done by making 20mx20 m measuring plot with in old coast sheoak (over 20 years), mid age (10-20) and young (under 10 years) in three different locations: Cemara cave, shrimp pond, and lighthouse. Plot in each location is far from coast when it is 50m from coastal line and near coast when it is less than 50 m from coat line. Amount of plot in each location from 2 through 6 plots depending on planting area at age observed in each location. Variable observed was amount of bag worm categorized using core in each observational unit (tree). Result of scoring was used to calculate distribution area and intensity of bag worm in each age in the three locations. The data was then analyzed qualitatively descriptively to determine tendency in each age and location. The result indicated that the greatest distribution area and intensity of bag worm is in young and mid coast sheoak, in shrimp pond and near coast. Distribution area and intensity of bag worm in coast sheoak in different ages, locations and distances from coast is also influenced by sunshine at morning and day that can reach crown of coast sheoak